Psychological issues in breast cancer survivors confronted with motherhood: Literature review and a call to action - Valentina Elisabetta Di Mattei; Valentina Elisabetta Di Mattei; Gaia Perego; Gaia Perego; Paola Taranto; Martina Mazzetti; Federica Ferrari; Noemi Derna; Fedro Alessandro Peccatori; Giorgia Mangili; Massimo Candiani; Massimo Candiani (Frontiers in Psychology, 2023)
Breast cancer is currently the most common cancer among women worldwide; in 15–25% of cases, patients are premenopausal at the time of diagnosis, and 50% of women desire pregnancy after cancer diagnosis. Motherhood after breast cancer involves complex psychological challenges with long-term consequences, though it is safely pursuable with adequate support. The purpose of this mini-review is to analyze the psychological implications surrounding pregnancy and motherhood after breast cancer and promote action in addressing the challenges that might affect women facing these life events.